Na vyftig jaar Vrye Gereformeerde Kerk Kaapstad – kerk of sekte? - Breytenbach, JA (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
After fifty years Vrye Gereformeerde Kerk Kaapstad – church or sect? The Vrye Gereformeerde Kerk Kaapstad (Free Reformed Church of Cape Town) was instituted on 2 March 1952. It was instituted by eleven men and women who were immigrants from the Netherlands and who were members of the Gereformeerde Kerken in Nederland that liberated themselves in 1944 from the false doctrine and authority of synod. The theological and critical question is: was a church or a sect founded in 1952? The article evaluates the applicable documents and concludes that these believers had no intention to seperate themselves because of an idea or group identity, or because they disliked the Afrikaans reformed churches, but they longed to obey Christ and His Word, and wanted to find unity with all who hold to the pure doctrine of the gospel.